PENGARUH PENAMBAHAN MOLYBDENUM (Mo) DAN NIKEL (Ni) TERHADAP STRUKTUR MIKRO, UJI KEKERASAN DAN KETAHANAN AUS BESI COR KELABU - Sulistyo Endri Purwanto; Sugeng Tirta Atmadja (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
Grey cast iron is kind of material that mostly used in parts and spare parts vehicle industries. One among of them is engine block. By using, engine block receive repeated frictions or dynamic load. This process takes place naturally and is not characteristic basic material. But, the material response to external systems when there are surfaces rub against each other. Resulting in increased material loss caused by the relative movement of objects. Therefore, to increase the wear endurance of grey cast iron, the addition of element molybdenum and nickel.There are three speciments tested in this experiment, base material (0,02 % Mo and 0,07% Ni), mixture 1 (0,15 Mo and 0,17 % Ni), and mixture 2 (0,12 % Mo and 0,22 % Ni). Chemical composition test by using spectrometer, testing to determine the micro structure micrographic, hardness test in Rockwell A that be conversed to Brinell, and wear test by using pin on disk tipe.The results showed that an increase in the mechanical properties of gray cast iron after the addition of molybdenum and nickel is the value of hardness are increased in series 197,14 HB, 213,33 HB, and 205,52HB. While the percentage obtained for the wear test material, base material loss of 0,0007 %, 0,0001 of mixture 1 and 0,0008 % of mixture 2.